Pola Pembangunan Karakter Perspektif Al-Qur’an (Kajian Tematik Terhadap Surah Lukman) - Juwariyah Juwariyah (Mukaddimah: Jurnal Studi Islam, 2016)
The character is the human values that was related by the single one God, the self, the human being, the milieu and the nationality that meterialize at idea, attitude, opinion, words and behavior that be based on the religion standard, law, etquette, culture, and a beauty. So, the character is the appear behavior in the every day life, both at the attitude or the measure, because the character is the totality from the external human condition, so the human with out character will be giving a significant negative impact, both to the self or the scope around. Therefore the reserarch to al-Qur’an perspectiv in the character building is done, to give an information and all solution at once, haw Got have give an example to build the human character to became a good agen of God. This research was describe haw the Lukman Hakim human gived the character education to the litle children begin with a faith, service to the parents, obedient to be religious, be patient, and be not arrogant.